Pembuatan Permainan Puzzle untuk Bacaan Anak Kelas Rendah Sekolah Dasar - Herman, Rafika; Rahmah, Elva (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2017)
This paper discussed how to make a puzzle that can be used by students both play and learn at the same time. The purpose of this paper is to describe the making of anatomical human body puzzle for beginner students in Elementary School. The data were collected through observation, interview, and literature study. The data analysis was done by the qualitative descriptive method.Based on discussion, the step of making puzzle is (1) Determining the topic, (2) Gathering all kinds of required information, (3) Desirable puzzle design, (4) Draw the picture on other HVS paper with pen or pencil, (5) Group the pictures based on the groups, the pictures were coloring with the students’ favorite color, (6) cut the pictures and divided into some parts, (7) The pictures were arranged into the provided cardboard background, (8) ) The picture can be wrapped using a clear colored plastic.The Usefulness of the puzzle in SDN 04 Koto Ranah can be well categorized because of the students’ readiness, attention to the teacher’s explanation about the puzzle, regularly in finding the puzzle pieces, the spirit in complete the puzzle pieces, asking the teacher whether the students' do not understand or have difficulties when crafting the puzzle, doing the tasks given by the teacher.Keyword: ability to read, puzzle, Elementary School